Vivo wound healing performance of halloysite clay and gentamicin-incorporated cellulose ether-PVA electrospun nanofiber mats - Wali, Ashwini; Gorain, Mahadeo; Inamdar, Satish; Kundu, Gopal; Badiger, Manohar V. (ACS Applied Bio Materials, 2019)
Wound healing is a dynamic and complex process that requires a suitable environment to enhance the rapid healing process. In this context, fabrications of nanofibrous materials with antibiotic and antibacterial properties are becoming extremely important. In this present work, we report on the fabrication and characterization of electro-spun cellulose ether-PVA nanofiber mats loaded with halloysite clay (HNT) and gentamicin sulfate (GS) for faster wound healing applications. The morphology of nanofiber mats was examined by SEM and TEM. The average diameter of the nanofiber mats were in the range of 325 ± 30 nm. The physicochemical characterizations were done by FT-IR and XRD, which reveal the presence of HNT and GS into the nanofibers. The incorporation of halloysite gave good mechanical strength to the nanofiber mats. Swelling studies indicated the hydrophilicity of the mats. In vitro studies revealed that HNTs are nontoxic to L929 fibroblast cells and also promote cell growth and proliferation. The antibacterial property of HNT was also studied. The slow release of GS from the nanofiber mats was observed for a period of 18 days. The in vivo wound healing studies on the wistar rats for 21 days revealed the wound healing faster within 2 weeks by the incorporation of HNT and GS into the nanofiber mats and hence these nanofiber mats show great potential in acute and chronic wound healing applications.